Perspectives of HRM Professionals on Diversity, Equity, and Inclusion in Nepal (Far Western Review, 2023)
Diversity Management has not yet been a significant part of now much discussed topic HRM in Nepal although the concepts of Diversity Management (DM) emerged in the USA, Canada in 1980s. Most of the developed countries in European Union have been the flagship of diversity management. There is handful of renowned organizations today either catering HRM services or implementing full-fledged HRM discipline in their own organizations. College text books and, seminars and dialogues conducted by development sectors have indicated that the emergence of concepts of Diversity, Equity and Inclusion (DEI) is pertinent in today’s context. In developed countries, both profit making and non-profit making organizations have been emphasizing the concepts of DEI and focusing on those in organizations. It’s a thought[1]provoking idea to learn the perspectives of current organization leaders in Nepal about their views on DEI. The article has been prepared based on findings of in-depth interviews taken with leaders and/or senior HR managers of reputed companies those are promoting HRM in Nepal. It attempts to provide an exploratory review seeking to shed light on their perspectives of regarding DEI in their pre-established HRM domain. The article explores the opinions, experiences and competencies and the initiatives taken by HRM leaders. The article also discusses the challenges faced by the HRM leaders in the pursuit of promoting the diversity management.